Pengaruh perbedaan kombinasi formulasi minuman fungsional tinggi serat terhadap sifat fisikokima dan sensori - Muhammad Arkan Fandewa; Muhammad Said Siregar; Norzaleha Kasim; Maisarah Shamsulkamal (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2026)
Fiber drinks are specially formulated to help increase daily fiber intake. High-fiber drinks have the potential to become functional beverages with high fiber content and better acceptance, in order to understand their physicochemical characteristics, viscosity, pH, total dissolved solids, total dietary fiber, and sensory evaluation. This study has 3 different formulations that are intended to be tested. Formulation 1 contains a combination of several types of fruit and vegetable purees along with some hydrocolloids in the following proportions: Dragon Fruit Puree 18%, Pineapple Puree 23.4%, Roselle Puree 4.6%, Beetroot Puree 8%, Inulin 0.3%, Arabic Gum 0.2%, and FOS 0.5%. Formulation 2 contains a combination of: Dragon Fruit Puree 20%, Pineapple Puree 15%, Roselle Puree 4%, Beetroot Puree 4%, Inulin 0.5%, Arabic Gum 0.5%, and FOS 0.1%. Formulation 3 contains a combination of: Dragon Fruit Puree 15%, Pineapple Puree 11%, Roselle Puree 4%, Beetroot Puree 2%, Inulin 0.5%, Arabic Gum 0.5%, FOS 0.5%, Polydextrose 1.0%, and Resistant Dextrin 0.5%. This study aims to determine the effect of different combinations of high-fiber functional drink formulations on physicochemical and sensory properties. The results showed that the differences in formulation combinations had a significant effect on pH, with formulation 3 having the highest pH (4.68). Analysis of total dissolved solids showed that formulation 1 had the highest value (7.70). Total dietary fiber analysis indicated that formulation 3 had the highest value (5.20), while the highest viscosity was recorded in formulation 1 with a value of (3.45). Sensory analysis results showed a higher preference for formulation 2. The study concluded that formulation 2 is the best formulation, as it is able to achieve an optimal balance between physicochemical characteristics and sensory quality. This study provides an important contribution to the development of high-fiber functional beverage products that not only offer many benefits but also liked by consumers.